Enterprise Risk Managemenut (ERM) and Corporate Value in Indonesia - Poppy Camenia Jamil; Sinta Yulyanti; Ary Prabowo (Jurnal Ekonomi KIAT, 2024)
Enterprise Risk Management (ERM) create value added for the company by facilitate management in controling various risk which caused uncertainties condition by integrating all types of risk using integrated tools and tachniques, and then cordinate thr activites of risk management to all operating unit within an organization so that all types of risk can be minimized. The implementation of Enterprise Risk Management (ERM) of the firm. The objectives of this research is to identify the effect of Enterprise Risk Management (ERM) and firm size, ROA, and manajerial ownership as control variables on firm value that is proxied by Tobin’s Q. population of this research was manufacturing companies listed in indonesia stock exchange (IDX) in 2019-2020. The used method in this researc is multiple linier Regression-Ordinary Last Square ( OLS) and hypotheses testing using t-test to test the regresion coefficients with level of signification of 5%. Results showed that Enterprise Risk Management (ERM) hassignificant positive effect on the firm value. Size of the company has significant positive effect on the firm value. ROA has significant positive effect on the firm value. While the managerial owner shipe has significant negative effect on the firm value.